ATTENTION ASSISTANCE IN SICKLE DISEASE: LITERATURE REVIEW - Silva, Felipe Pereira da; Abreu, Clezio Rodrigues de Carvalho (Revista Coleta Científica, 2021)
The aim of this study is a literary review and to analyze the clinical aspects of sickle cell anemia with the attention of the pharmacist in relation to this disease. A literature review was carried out using Pubmed, Lilacs, Scielo, and Virtual Health Library (VHL) databases. Using texts available in Health Education, which is an essential tool to make patients aware of the characteristics of the disease and promote the correct use of medicines. The research is justified on the role of pharmaceutical care in Sickle Cell Disease in general. The results of this study can serve as support to the literature or even to Organs competent bodies of hospital sectors for implementations and improvements in health.